DSM : a history of psychiatry's bible - Horwitz, Allan V. (Johns Hopkins University Press, 2021)
"This book tells a history of the Diagnostic and Statistical Manual of Mental Disorders (DSM), known as "psychiatry's bible." It has been at the center of thinking about mental health in the United States since it was first published in 1952. The author covers its various editions and their cultural and political effects"--